2013
DOI: 10.5194/acp-13-4563-2013
|View full text |Cite
|
Sign up to set email alerts
|

Variability in the speed of the Brewer–Dobson circulation as observed by Aura/MLS

Abstract: Abstract. We use Aura/MLS stratospheric water vapour (H2O) measurements as tracer for dynamics and infer interannual variations in the speed of the Brewer–Dobson circulation (BDC) from 2004 to 2011. We correlate one-year time series of H2O in the lower stratosphere at two subsequent pressure levels (68 hPa, ~18.8 km and 56 hPa, ~19.9 km at the Equator) and determine the time lag for best correlation. The same calculation is made on the horizontal on the 100 hPa (~16.6 km) level by correlating the H2O time seri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
75
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(79 citation statements)
references
References 45 publications
(69 reference statements)
4
75
0
Order By: Relevance
“…The QBO is closely related to the tropical upwelling Flury et al (2013). A regression of temperature differences onto the differences in the vertical component of BDC between the Natural and NOQBO run shows a very similar result than the regression of temperature differences onto the QBO time series (not shown).…”
Section: Summary and Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The QBO is closely related to the tropical upwelling Flury et al (2013). A regression of temperature differences onto the differences in the vertical component of BDC between the Natural and NOQBO run shows a very similar result than the regression of temperature differences onto the QBO time series (not shown).…”
Section: Summary and Discussionmentioning
confidence: 53%
“…The temperature in the TTL is determined by the combined influences of latent heat release, thermally as well as dynamically driven vertical motion and radiative cooling (Gettelman and Forster, 2002;Fueglistaler et al, 2009;Grise and Thompson, 2013). The thermal structure, static stability and zonal winds in the TTL affect the two-way interaction between the troposphere and the stratosphere (Flury et al, 2013;Simpson et al, 2009) as well as the surface climate, since the relative minimum temperature (usually known as the cold point tropopause) subsequently influences the radiation and water vapour budget (Andrews, 2010). The TTL reacts particularly sensitively to anthropogenically induced radiative, chemical and dynamical forc-…”
Section: Introductionmentioning
confidence: 99%
“…However, their results showed that the difference in CO 2 mole fraction between the middle and lower stratosphere was about 7−8 ppm, which is twice as large as our finding obtained in the Antarctic stratosphere. Such a latitude-dependent vertical CO 2 difference could be mainly related with the effects (1) that the mole fraction of upper tropospheric CO 2 is higher in the northern hemisphere than in the southern hemisphere on average (Matsueda et al 2015) and the tropospheric and stratospheric air exchange occurs through various processes, such as blockings, cut-off cyclones, and tropopause folds (e.g., Holton et al 1995), and (2) that the tropospheric air with high CO 2 mole fractions, intruded into the stratosphere in the tropics, has a stronger influence on lower stratospheric CO 2 in northern midlatitudes than in Antarctica, since its poleward transport through the lower stratosphere is faster in the northern hemisphere than in the southern hemisphere (Flury et al 2013). …”
Section: Methodsmentioning
confidence: 99%
“…Poleward of the subtropical jet, water may be transported into the lowermost stratosphere through isentropic troposphere-stratosphere exchange (Holton et al, 1995) or through convective overshoot of the local tropopause Hanisco et al, 2007;Liu at el., 2008;Liu and Liu, 2016). Isentropic transport from the tropics is the dominant pathway for water into the lowermost stratosphere, with evidence from the seasonal cycle of lower stratospheric water (e.g., Flury et al, 2013). How important the sublimation of ice from convective overshoot is for hydrating the stratosphere is a topic of ongoing debate (e.g., Randel et al, 2015;Wang, 2003).…”
Section: Introductionmentioning
confidence: 99%